About interpolation of subspaces of rearrangement invariant spaces generated by Rademacher system - Sergey V. Astashkin (International Journal of Mathematics and Mathematical Sciences)
The Rademacher series in rearrangement invariant function spaces close to the space L∞ are considered. In terms of interpolation theory of operators, a correspondence between such spaces and spaces of coefficients generated by them is stated. It is proved that this correspondence is one-to-one. Some examples and applications are presented.